Evaluation of Factors Related to Glycemic Management in Professional Cyclists With Type 1 Diabetes Over a 7-Day Stage Race - Richard Bracken (Diabetes Care, 2020)
OBJECTIVE To investigate factors related to glycemic management among members of a professional cycling team with type 1 diabetes over a 7-day Union Cycliste Internationale World Tour stage race.RESEARCH DESIGN AND METHODS An observational evaluation of possible factors related to glycemic management and performance in six male professional cyclists with type 1 diabetes (HbA1c 6.4 ± 0.6%) during the 2019 Tour of California.RESULTS In-ride time spent in euglycemia (3.9–10.0 mmol/L glucose) was 63 ± 11%, with a low percentage of time spent in level 1 (3.0–3.9 mmol/L; 0 ± 1% of time) and level 2 (<3.0 mmol/L; 0 ± 0% of time) hypoglycemia over the 7-day race. Riders spent 25 ± 9% of time in level 1 (10.1–13.9 mmol/L) and 11 ± 9% in level 2 (>13.9 mmol/L) hyperglycemia during races. Bolus insulin use was uncommon during races, despite high carbohydrate intake (76 ± 23 g ⋅ h−1). Overnight, the riders spent progressively more time in hypoglycemia from day 1 (6 ± 12% in level 1 and 0 ± 0% in level 2) to day 7 (12 ± 12% in level 1 and 2 ± 4% in level 2) (χ2[1] > 4.78, P < 0.05).CONCLUSIONS Professional cyclists with type 1 diabetes have excellent in-race glycemia, but significant hypoglycemia during recovery overnight, throughout a 7-day stage race.